2018
DOI: 10.1016/j.celrep.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A Causes Tau/APP Phosphorylation, Synaptopathy, and Memory Deficits in Alzheimer’s Disease

Abstract: SUMMARY Protein phosphatase 2A (PP2A) inhibition causes hy-perphosphorylation of tau and APP in Alzheimer’s disease (AD). However, the mechanisms underlying the downregulation of PP2A activity in AD brain remain unclear. We demonstrate that Cancerous Inhibitor of PP2A (CIP2A), an endogenous PP2A inhibitor, is overexpressed in AD brain. CIP2A-mediated PP2A inhibition drives tau/APP hyperphosphorylation and increases APP β-cleavage and Aβ production. Increase in CIP2A expression also leads to tau mislocalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 45 publications
1
64
0
1
Order By: Relevance
“…Treatment with this apoE-mimetic peptide suppressed microglial activation and secretion of inflammatory mediators (e.g., TNF-α and IL-6 proteins) in primary microglial cultures and microglial cell lines: ApoE is an antagonist of SET protein (Christensen et al 2011b). CIP2A-mediated PP2A inhibition drives tau/APP hyperphosphorylation and increases APPβ-cleavage and Aβ production (plaques) between neurons (Shentu et al 2018). Both the enhancing endogenous PP2A activity and the antagonizing SET and CIP2A reduce levels of phosphorylated kinases and inflammatory response with TNF-α, IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment with this apoE-mimetic peptide suppressed microglial activation and secretion of inflammatory mediators (e.g., TNF-α and IL-6 proteins) in primary microglial cultures and microglial cell lines: ApoE is an antagonist of SET protein (Christensen et al 2011b). CIP2A-mediated PP2A inhibition drives tau/APP hyperphosphorylation and increases APPβ-cleavage and Aβ production (plaques) between neurons (Shentu et al 2018). Both the enhancing endogenous PP2A activity and the antagonizing SET and CIP2A reduce levels of phosphorylated kinases and inflammatory response with TNF-α, IL-1 and IL-6.…”
Section: Discussionmentioning
confidence: 99%
“…Beta spectrin has been identified as an integral component of beta-amyloid plaques in Alzheimer’s disease (AD) and spectrin breakdown products (SBDPs) have been implicated as potential biomarkers for neurodegenerative diseases including AD [49], [50]. In a recent study of AD, CIP2A was found to be overexpressed and associated with tau hyperphosphorylation, mis-localization and AD-related cellular pathology [14]. In mice, overexpression of CIP2A in the brain induced AD-like cognitive deficits [14].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study of AD, CIP2A was found to be overexpressed and associated with tau hyperphosphorylation, mis-localization and AD-related cellular pathology [14]. In mice, overexpression of CIP2A in the brain induced AD-like cognitive deficits [14]. Future studies may determine whether CIP2A interaction with beta-spectrin modulates protein aggregation in AD pathology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The upregulation of APP T668 phosphorylation could also be a consequence of the deactivation of protein phosphatase (PP) in vivo. AD patients have an increased level of cancerous inhibitor of protein phosphatase 2A (CIP2A) compared with that of age-matched controls [79]. CIP2A inhibits the activity of PP2A and promotes APP T668 phosphorylation, triggering the β-cleavage of APP, Aβ production, and tau hyperphosphorylation [79].…”
Section: App Phosphorylationmentioning
confidence: 99%